DEVELOPMENT OF ISLAMIC CULTURAL HISTORY TEACHING MATERIALS BASED ON MULTILITERACY TO ENHANCE STUDENT LEARNING OUTCOMES ACHIEVEMENT IN MADRASAH TSANAWIYAH - Maruhawa, Arenibi; Ananda, Rusydi; Arsyad, Junaidi (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: The learning process of Islamic Cultural History still adheres to the old paradigm, where teachers passively transfer knowledge to students. Purpose: The purpose of this research is to enhance understanding and productivity through the development of teaching materials. Method: This study adopts a research and development (R&D) approach, employing analysis techniques to assess the feasibility, practicality, and effectiveness of the teaching materials. Result: The results indicate that, on average, the proportion of time teachers spend explaining instructional materials to students is 24.70% of the available time for each session. The average percentage of time teachers spend summarizing instructional materials and providing reflections is 12.60%. Additionally, the average percentage of time teachers spend responding to student questions is 12.10%, while the average percentage of time teachers spend asking questions to students is 10.20% of the allocated time for each session. Conclusion: Therefore, multiliteracy-based instructional materials for Islamic Cultural History can be considered a new paradigm in education. This is because these materials are developed through research and development activities and have been proven to demonstrate an improvement in students' learning outcomes.Top of Form